Application of the Principles of Transparency and Accountability in the Use of Public Funds: Legal Review of Law no. 2 of 2017 - Evangelista, Beverly; Sumaragatha, I Gusti Bagus Sakah; Mulyana, Septira Putri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Management of public funds in infrastructure projects in Indonesia is an important aspect that influences national development. Transparency and accountability in the use of public funds are the main focus, especially in accordance with Law no. 2 of 2017 concerning Construction Services. This article aims to analyze the application of these principles in the management of public funds. The research method used is normative research, which includes literature studies, legal document analysis, and case studies to evaluate the effectiveness of regulations in increasing transparency and accountability. The discussion includes an analysis of the legal norms governing the management of public funds as well as the challenges faced in their implementation. The research results show that although Law no. 2 of 2017 provides a clear legal framework, there are still weaknesses in implementing the principles of transparency and accountability, which could potentially lead to misuse of funds. The conclusion of this article emphasizes the need to strengthen regulations and more effective monitoring mechanisms to ensure efficient and responsible use of public funds, as well as increase public trust in the management of public funds.